Age‐friendly care in the Veterans Health Administration: Past, present, and future. Issue 1 (17th October 2022) - Farrell, Timothy W.; Volden, Tiffany A.; Butler, Jorie M.; Eleazer, G. Paul; Rupper, Randall W.; Echt, Katharina V.; Shaughnessy, Marianne; Supiano, Mark A.
Abstract: The Veterans Health Administration (VHA) has long recognized the need for age‐friendly care. VHA leadership anticipated the impact of aging World War II veterans on VA healthcare systems and in 1975 developed Geriatric Research, Education, and Clinical Centers (GRECCs) to meet this need. GRECCs catalyzed a series of innovations in geriatric models of care that span the continuum of care, most of which endure. These innovative care models also contributed to the evidence base supporting the present‐day Age‐Friendly Health Systems movement, with which VHA is inherently aligned. As both a provider of and payor for care, VHA is strongly incentivized to promote coordination across the continuum of care, with resultant cost savings. VHA is also a major contributor to developing the workforce that is essential for the provision of age‐friendly care. As VHA continues to develop and refine innovative geriatric models of care, policymakers and non‐VHA health care systems should look to VHA programs as exemplars for the development and implementation of age‐friendly care.